Nesfatin-1 and Ghrelin/GOAT as Potential Biomarkers in Adolescent Headache with Temporomandibular Disorders: A Cross-Sectional Study - Sojka, Anna; Dorocka-Bobkowska, Barbara; Bartosik, Yasmin; Yetkin, Ozgun; Steinborn, Barbara; Żarowski, Marcin (Journal of Medical Science, 2025)
Introduction. Nesfatin-1 and Ghrelin O-acetyltransferase (GOAT) are peptide hormones involved in stress response and pain modulation beyond their metabolic functions. This study investigated whether these biomarkers differ between adolescents with headaches and healthy controls and examined their relationship with temporomandibular disorders (TMD).Material and methods. This cross-sectional study measured Nesfatin-1 and Ghrelin/GOAT levels in the serum and saliva of 44 adolescents with headaches (aged 10-17 years, diagnosed per ICHD-3 beta criteria) and 20 age-matched healthy controls. TMD was assessed using the Diagnostic Criteria for TMD (DC/TMD). Statistical comparisons were performed using non-parametric tests, with significance set at p < 0.05.Results. Nesfatin-1 was elevated in all headache patients compared to controls in both blood (patient median range: 39.5-45.0 ng/mL vs. control median range: 8.1-9.0 ng/mL, p
Keywords: nesfatin-1; ghrelin/GOAT; headache; temporomandibular disorders; adolescent